Determination of three-dimensional joint loading within the lower extremities in snowboarding - Krüger, A.; McAlpine, P.; Borrani, F.; Edelmann-Nusser, J. (Journal of Engineering in Medicine, 2012)
In the biomechanical literature only a few studies are available focusing on the determination of joint loading within the lower extremities in snowboarding. These studies are limited to analysis in a restricted capture volume due to the use of optical video-based systems. To overcome this restriction the aim of the present study was to develop a method to determine net joint moments within the lower extremities in snowboarding for complete measurement runs. An experienced snowboarder performed several runs equipped with two custom-made force plates as well as a full-body inertial measurement system. A rigid, multi-segment model was developed to describe the motion and loads within the lower extremities. This model is based on an existing lower-body model and designed to be run by the OpenSim software package. Measured kinetic and kinematic data were imported into the OpenSim program and inverse dynamic calculations were performed. The results illustrate the potential of the developed method for the determination of joint loadings within the lower extremities for complete measurement runs in a real snowboarding environment. The calculated net joint moments of force are reasonable in comparison to the data presented in the literature. A good reliability of the method seems to be indicated by the low data variation between different turns. Due to the unknown accuracy of this method the application for inter-individual studies as well as studies of injury mechanisms may be limited. For intra-individual studies comparing different snowboarding techniques as well as different snowboard equipment the method seems to be beneficial. The validity of the method needs to be studied further.